PEMBUATAN FRUITGHURT DARI LAPISAN PUTIH (Mesocarp) KULIT SEMANGKA (Citrullus vulgaris) BERDASARKAN LAMA FERMENTASI DAN ANALISIS POTENSI RANCANGAN LEMBAR KERJA SISWA PADA PEMBELAJARAN BIOLOGI SMA - Indri Rahmawati; Darmawati '; Imam Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to know the quality fruitghurt of white layer (mesocarp) leather watermelon (Citrullus vulgaris) based on long fermentation and potential that could be developed on a learning process biology high school. This research consists of two stage. The first stage of research that is making fruitghurt of white layers (mesocarp) a leather watermelon using the experimental method with draft randomized completely (RAL), which consists of 5 treatments and 3 replications. Parameters that observed is levels of lactid acid, pH, the reduction of sugar content, the water level and organoleptic test. The results of research obtained then analyzed ANOVA and a further test DMRT at 5% level. The second stage is the phase design (draft) Student Worksheet (LKS) sourced from the results of the first phase. The research result show that long fermentation to exert an influence on is real levels of lactic acid, pH, sugar reduction , the water level and, and organoleptic test. Long fermentation 96 hours is long fermentation best to produce fruitghurt of white layers (mesocarp ) a leather watermelon quality. Where produce levels lactic acid 0.80 % , sugar reduction 7,30 % , the water level 82,59 % and 2.9 pH levels. The lactic acid that produced that produced had filled the quality in accordance SNI 01-2981-1992 is so much as 0.5%-2.0%. As for organoleptic texture, color, aroma and flavor contained in the fermentation 96 hours. The results of the study can be used as design student worksheet (LKS) in insubject matter the outcomes of the implications of biotechnology on salingtemas the sub material with conventional biotechnology.Keywords : Fruitghurt, White layer (mesocarp) Leather Watermelon, Long Fermentation, The Design LKS